Violence and crime in Mexico: the political use of fear - Mendieta Ramírez, Araceli (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
It is a discussion about the plurality of violence, understood as a cultural construct. We are mainly talking about two dimensions of violence: direct and structural. The first dimension is usually the most notorious, because it implies the intentional action of harm between two or more subjects, while the second is more silent and invisible, because it has been standardized and preserved in economic, political and cultural systems, as in the case of inequality with effects on the inherited disadvantages of certain sections of the population. Both dimensions are usually treated independently, but are indissoluble, intersect and generate a plurality of forms and effects that public policies have failed to mitigate; consequently, social degradation is progressive in the territories. In Mexico, direct violence and its manifestation in crime has been a justification for the political use of fear, in order to impose political agendas, persuade citizens and legitimize security actions; all this, without being able to compensate the manifestations of the violence, not the delinquency.